PSYCHOLOGICAL AND PAIN PROCESSING FACTORS IN PATELLOFEMORAL PAIN: SEX DIFFERENCES AND CORRELATION WITH CLINICAL OUTCOMES - da Silva, Júlia de Cássia Pinto [UNESP]; Botta, Ana Flavia Balotari [UNESP]; Briani, Ronaldo Valdir [UNESP]; Del Priore, Liliam Barbuglio [UNESP]; de Azevedo, Fábio Mícolis [UNESP] (Elsevier, 2024)
Background Patellofemoral pain (PFP) is a multifactorial condition involving psychological factors (e.g. kinesiophobia and catastrophism) and pain processing factors (eg, hyperalgesia), which seem to be increased in individuals with PFP. Studies suggest that these factors appear to differ between men and women in other populations. Considering that PFP is twice as prevalent in females as in males, it is possible that sex influences psychological and pain processing factors and their relationship with clinical outcomes (e.g. pain and function) in individuals with PFP. Objectives The aim of this study was to compare the levels of kinesiophobia, catastrophism and pain pressure threshold (PPTs) between men and women with and without PFP and to investigate whether these outcomes are correlated to pain, function, and quality of life (QoL) in men and women with PFP. Methods 65 women and 38 men with PFP, 30 women and 30 men without PFP aged 18-40 years were enrolled in this cross-sectional study. The levels of kinesiophobia, catastrophism, pain, function and QOL were assessed by the Tampa Scale of Kinesiophobia, Pain Catastrophizing Scale, Visual Analog Pain Scale, Anterior Knee Pain Scale and the Medical Outcome Short-Form 36, respectively. PPTs were obtained with a digital algometer on the contralateral shoulder and patella. Generalized linear models (GzLM) were used for comparison analyzes while Spearman's test was used for correlation analyses. Results Women and men with PFP had greater kinesiophobia (CI: 1.88, 10.33; 1.55, 10.37), catastrophism (CI: 4.90, 14.01; 8.63, 27.78) and smaller Patellar PPTs (CI: -1.71, -.36; -1.43, -.04) compared to asymptomatic controls. Women with PFP had lower shoulder PPTs than men with PFP (CI: -1.89, -.74), which was not observed for psychological factors. In women with PFP, kinesiophobia and catastrophism correlated with pain (rho= .44 to .53), function (rho= -.55 to -.58) and the physical component of QoL (rho= -.63 to -.65). For men with PFP, only catastrophizing correlated with pain (rho= .42) and function (rho= -.43). Patellar and shoulder PPTs had only weak correlations with pain, function and QoL. Conclusion Individuals with PFP showed alterations in psychological and pain processing factors when compared to asymptomatic controls, although the presentation of psychological factors did not differ between genders, only for PPTs. However, it is important to note that psychological factors correlated differently with clinical outcomes in men and women with PFP. Implications Interventions focused on psychological and pain processing factors are recommended for individuals with PFP. Our results corroborate with these recommendations. Furthermore, our results are the first to indicate that interventions focused on kinesiophobia may be especially important for women with PFP, since higher levels of kinesiophobia are not directly correlated to worse levels of pain and function in men with PFP. Future clinical studies are needed in this area.